2021
DOI: 10.1002/slct.202004026
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Electrocatalyst for Oxygen Evolution Reaction: DFT Investigation on Transition Metal‐Tetracyanoquinodimethane Monolayer

Abstract: To search for efficient electrocatalyst towards oxygen evolution reaction (OER) for sustainable energy production, a family of transition metal-tetracyanoquinodimethane (TM-TCNQ) (TM = Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Ru, Rh, Pd)monolayers have been studied by first principle based density functional theory (DFT) computations. The systematic investigations on various TM-TCNQ structures revealed that Ni-TCNQ monolayer exhibits best catalytic activity towards OER. At equilibrium potential (1.23 Vvs RHE), the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…( 4 ) and ( 5 ) respectively) presented an uphill process in the absence of an applied bias U. Similar to pristine ZIS, OER4 was observed to be the RDS at the standard equilibrium potential for OER (U = 1.23 V) with a value of 5.123 V. It is noteworthy that even though P-doping reduced the overpotential by 0.024 V and out-performed pristine ZIS in the OER intermediate steps, the high (> 1 V) indicated that P-ZIS was not energetically efficient in promoting OER for O 2 production via overall water splitting 56 . Owing to the infeasibility of OER4’s uphill process, the HOO* radical is anticipated to undergo oxidative recombination with H + to produce H 2 O 2 instead 59 , 60 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 4 ) and ( 5 ) respectively) presented an uphill process in the absence of an applied bias U. Similar to pristine ZIS, OER4 was observed to be the RDS at the standard equilibrium potential for OER (U = 1.23 V) with a value of 5.123 V. It is noteworthy that even though P-doping reduced the overpotential by 0.024 V and out-performed pristine ZIS in the OER intermediate steps, the high (> 1 V) indicated that P-ZIS was not energetically efficient in promoting OER for O 2 production via overall water splitting 56 . Owing to the infeasibility of OER4’s uphill process, the HOO* radical is anticipated to undergo oxidative recombination with H + to produce H 2 O 2 instead 59 , 60 .…”
Section: Resultsmentioning
confidence: 99%
“…In short, OER consists of 4 elementary reaction steps (OER1, OER2, OER3 and OER4) as listed in Eqs. ( 2 – 5 ) 43 , 56 : where * represents the surface active site, and X* denotes an adsorbed intermediate (X) on the surface active site. The Gibbs free energy for each OER reaction step (∆G OER ) was evaluated based on the corresponding E f of each component and correction factors based on DFT computation 43 , 56 58 (see Supplementary Information online for calculation details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the overpotential was reduced greatly in Co@TBB-phen in comparison with TBB-phen, thereby signifying the role of cobalt in COPs. 79 Due to the unfilled d-orbitals of cobalt, it acts as a center of the electrophilic attack, and, with sufficient delocalization, the OER proceeds at lower overpotentials, which was challenging to achieve in metal-free TBB-phen. DFT computations were also performed to obtain a fundamental understanding of the HER process.…”
Section: Resultsmentioning
confidence: 99%